UPAYA HUKUM KASASI PENIPUAN PENGALIHAN OBJEK JAMINAN FIDUSIA TANPA PERSETUJUAN - Marsella Oktaviani; Aminah Aminah (Universitas Sriwijaya, 2024)
The legal relationship between creditors receiving fiduciaries and debtors providing fiduciaries is trust. The creditor trusts that the debtor will not misuse the goods pledged as collateral and maintain the goods well under his control. This fraudulent trust creates problems if the debtor commits a criminal act of fraud by transferring the object of fiduciary collateral without the consent of the parties. Cassation is an extraordinary legal effort submitted by the parties to seek justice and rectify a decision that has permanent legal force where it is deemed that the application of the law contains errors or raises legal questions which is to maintain the unity of the application of the law without harming interested parties. The cassation attempt was made because it was not based on legal facts that were legally relevant legally and correctly and did not match the legal facts revealed before the court. The type of research carried out is normative research which uses statutory regulations to solve problems. The data used is secondary data and the data collection method in this research is library research. The data analysis used is qualitative data. Based on the results of the discussion of this research, the judge's considerations in handing down a decision regarding Supreme Court Decision Number 381 K/Pid/2023 fraud regarding the transfer of fiduciary collateral objects, based on Law Number 42 of 1999 concerning Fiduciary Guarantees by examining the evidence and the application of witnesses based on legal facts At the trial the defendant was found guilty of the third alternative charge and sentenced to one year and two months.